1984
DOI: 10.2151/jmsj1965.62.5_730
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Prediction of the Heavy Rainfall Vortex Over Eastern Asia Monsoon Region

Abstract: A series of numerical forecasts were carried out to investigate a heavy rainfall event over the monsoon region of Eastern Asia which was caused by a vortex formed over the Tibet Plateau during Summer. The ECMWF global grid point model was capable of predicting the vortex four days in advance.The importance of the moist processes in the development of the vortex was investigated by comparing the results from a moist and a dry (without latent heat) versions of the model. It was found that the low level jet assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Several case studies showed that the Baiu rainfalls over Japan are mainly caused by mesoscale organized cloud systems associated with Baiu frontal depressions (e. g., Matsumoto et al, 1970;Akiyama, 1971, 1974;Yoshizumi, 1977;Akiyama, 1978). It has been reported that many vortices form over the Tibetan Plateau during the summer monsoon, and some of them move eastward and bring rainfalls over the central China (Tao and Ding, 1981;Tao and Chen, 1986;Kuo et al, 1986;Chen and Dell'Osso, 1984;Murakami and Huang, 1984;Ma and Bosart, 1987). Ninomiya et al ( , 1989a and Akiyama (1984a, b) studied a long-lived cloud cluster which formed at the eastern foot of the Tibetan Plateau and caused intense rainfalls over China and Japan.…”
Section: Baiu Frontmentioning
confidence: 99%
“…Several case studies showed that the Baiu rainfalls over Japan are mainly caused by mesoscale organized cloud systems associated with Baiu frontal depressions (e. g., Matsumoto et al, 1970;Akiyama, 1971, 1974;Yoshizumi, 1977;Akiyama, 1978). It has been reported that many vortices form over the Tibetan Plateau during the summer monsoon, and some of them move eastward and bring rainfalls over the central China (Tao and Ding, 1981;Tao and Chen, 1986;Kuo et al, 1986;Chen and Dell'Osso, 1984;Murakami and Huang, 1984;Ma and Bosart, 1987). Ninomiya et al ( , 1989a and Akiyama (1984a, b) studied a long-lived cloud cluster which formed at the eastern foot of the Tibetan Plateau and caused intense rainfalls over China and Japan.…”
Section: Baiu Frontmentioning
confidence: 99%
“…The transverse secondary circulation across the Mei-Yu front is baroclinic in nature and enhanced by convective heating. This view on the LLJ development differs from the mass-momentum adjustment process driven by cumulus convection suggested by several authors (Chen and Dell'Osso 1984;Chou et al 1990;Hsu and Sun 1994;Chen et al 1998). This problem will be investigated quantitatively in this study.…”
Section: Introductionmentioning
confidence: 74%
“…4d) forecast time as the upper-level trough amplified with a stronger secondary circulation. It is apparent that during 1-2 June 1987, the upper-level circulations during the intensification of the LLJ is not maintained by the thermally direct circulation driven by convective heating as suggested by several authors (Chen and Chang 1980; Chen 1983; Chen and Dell'Osso 1984;and Chou et al 1990). This problem will be discussed further in later sections.…”
Section: Area-averaged Energeticsmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, baroclinic instability might instigate the generation of SWVs. The front between the warm and moist air from the south Á or more precisely from the Indochinese peninsula and the SCS Á and the cold and dry air from the mid-latitudes preconditions the development of SWVs (Chen and Dell'Osso, 1984). SWVs may take different tracks through China and the adjacent seas.…”
Section: Introductionmentioning
confidence: 99%